The little book of hygge [compact disc, unabridged] : Danish secrets to happy living - Wiking, Meik (Blackstone Audio ; HarperAudio, 2016)
The Danes are famously the happiest people in the world, and hygge is a cornerstone of their way of life. Hygge (pronounce Hoo-ga) loosely translates as a sense of comfort, togetherness, and well-being. You know hygge when you feel it. It is when you are cuddled up on the sofa with a loved one, or sharing comfort food with your closest friends. It is those crisp blue mornings when the light through your window is just right. It is about gratitude and savoring the simple pleasures in life. In short, it is the pursuit of everyday happiness.